ENT300 Business Plan Individual Assignment : SS Enterprise / Salma Abdullah Muhammad Masyhur Alhaddad - Abdullah Muhammad Masyhur Alhaddad, Salma (2020)
I am going to make a simple summary about my business plan. I planned to create a makeup set product for women which it cames from what I have been selling since I was 18 years old. I am sure that every women out there love about beauty. Actually makeup can be consists as cosmetics product but it is in specific. This makeup set box will come with a few sets that customers can choose. In this box there will be, foundation, blusher,eyeshadow,mascara, eyeliner, contour, lipstick, based makeup and sponge. Makeup is meant to enhance outer beauty without harming the skin. The skin is the largest organ of the body. It is a protective shell that needs to breathe and be nourished and nurtured. As part of a daily routine, most women use makeup to enhance their appearance. The ingredients of my makeup product will be from organics and do not harm the skin. It will also help to recover skin that has problem. This makeup set’s price will be affordable and can be used by women from every stage of ages. The best part is eventhough the skin is expose to sun or any weather or even water, it will not affect the makeup as it is long lasting makeup. This makeup set can be used by all skin types and skin colours. We will also offered the best ingredients, packaging and there will be a travel set as well. The quality of our product and what is the customers want and need will be as our priority The HQ of SS Enterprise will be based in Alor Setar, Kedah.